شاہدہ دلاور شاہ کا ناول "زندگی ایک ناراض متن" کا موضوعاتی مطالعہ (Contemporary Journal of Social Science Review, 2025)
"The novel, a word of Italian origin, is a mirror of society and history, regardless of the language In which it Is written. Based on the era and place it is written, it reflects the people, geographical background, historical landmarks, customs, traditions, culture, language, and every aspect of that environment.In Urdu literature, the novel Is a significant and unique genre of prose that explores various aspects of life, events, and issues in detail and with great interest. It presents life's diverse situations, events, and problems in a detailed and engaging manner."  حوالہ جات • شاہدہ دلاور شاہ ،ڈاکٹر، زندگی ایک ناراض متن ،لاہور، عکس پبلیکیشن، 2023,ص: 97• شاہدہ دلاور شاہ ، ڈاکٹر ،زندگی ایک ناراض متن ، لاہور ،عکس پبلیکیشن ،2023, ص: 17• شاہدہ دلاور شاہ ، ڈاکٹر ،زندگی ایک ناراض متن ،لاہور، عکس پبلیکیشن ،2023 ص21• شاہدہ دلاور شاہ ، ڈاکٹر ، زندگی ایک ناراض متن ،لاہور، عکس پبلیکیشن ، 2023,ص: 228• شاہدہ دلاور شاہ ، ڈاکٹر ، زندگی ایک ناراض متن ، لاہور ،عکس پبلیکیشن ، 2023,ص231• شاہدہ دلاور شاہ ، ڈاکٹر ، زندگی ایک ناراض متن ، لاہور ،عکس پبلیکیشن ، 2023, ص: 227• شاہدہ دلاور شاہ ، ڈاکٹر ، زندگی ایک ناراض متن ، لاہور ،عکس پبلیکیشن،2023,  ص: 238References:Shahida Dilawar Shah, Dr. Zindagi Aik Naraz Matn. Lahore: Aks Publication, 2023, p. 97.Shahida Dilawar Shah, Dr. Zindagi Aik Naraz Matn. Lahore: Aks Publication, 2023, p. 17.Shahida Dilawar Shah, Dr. Zindagi Aik Naraz Matn. Lahore: Aks Publication, 2023, p. 21.Shahida Dilawar Shah, Dr. Zindagi Aik Naraz Matn. Lahore: Aks Publication, 2023, p. 228.Shahida Dilawar Shah, Dr. Zindagi Aik Naraz Matn. Lahore: Aks Publication, 2023, p. 231.Shahida Dilawar Shah, Dr. Zindagi Aik Naraz Matn. Lahore: Aks Publication, 2023, p. 227.Shahida Dilawar Shah, Dr. Zindagi Aik Naraz Matn. Lahore: Aks Publication, 2023, p. 238.